Revision of the southern African genera Nemopterella Banks and Nemia Navás (Neuroptera: Nemopteridae: Nemopterinae), with descriptions of new genera and species - Abdalla, Ishtiag H.; Mansell, Mervyn W.; Sole, Catherine L. (Zootaxa, 2019)
The southern African genera Nemopterella Banks, 1910 and Nemia Navás, 1915 (Neuroptera: Nemopteridae: Nemopterinae) are revised. Nemopterella is split into three genera: Nemopterella sensu stricto with type species Nemopteryx africana Leach, 1815 (= Nemopterella africana), Afroptera gen. nov., with type species Nemopterella munroi Tjeder, 1967, and the monotypic genus Siccanda gen. nov., with type species Nemopterella arenaria Tjeder, 1967. Eight new species are described in Afroptera gen. nov.: A. acuta Abdalla & Mansell sp. nov., A. alba Mansell & Abdalla sp. nov., A. brinkmani Abdalla & Mansell sp. nov., A. balli Abdalla & Mansell sp. nov., A. cylindrata Abdalla & Mansell sp. nov., A. folia Abdalla & Mansell sp. nov., A. koranna Mansell & Abdalla sp. nov., A. maraisi Abdalla & Mansell sp. nov., as well as two new species in the genus Nemopterella: N. kabas Mansell & Abdalla sp. nov., and N.cedrus Mansell & Abdalla sp. nov.